The Relationship Between Self-Esteem and Family Support with Social Isolation in Patients with Diabetes Mellitus at Puskesmas Deli Tua - Rostiodertina Girsang; Rasninta Devi Ansela; Lidya Arni Januarita Simbolon; Zuliawati (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Individuals with chronic illnesses, particularly diabetes mellitus, often encounter psychological challenges such as a tendency toward social isolation. Several factors contribute to this condition, including self-esteem and the level of family support. This study aimed to examine the relationship between self-esteem and family support with social isolation among patients with diabetes mellitus at Deli Tua Health Center. An analytical research design with a cross-sectional correlational approach was employed. A total of 54 respondents were selected using simple random sampling. Data were collected through structured questionnaires and analyzed using the Chi-Square test. The findings revealed a significant association between self-esteem and social isolation (p = 0.000; < 0.05). These results indicate that individuals with higher self-esteem are less likely to experience social isolation.. This confirms that psychological resilience plays an important role in maintaining social functioning amid chronic illness. In conclusion, self-esteem serves as a key factor in reducing social isolation among patients with diabetes mellitus. Therefore, efforts to improve self-esteem through psychosocial support and nursing interventions should be prioritized to prevent social withdrawal in these patients.